Conformidade fiscal cooperativa: novas perspectivas para o relacionamento entre o fisco e o contribuinte - Cavalcante, Lucas Ernesto Gomes (2021)
The study aims to investigate the feasibility of cooperative fiscal compliance to reduce tax litigation in Brazil. The theme is based on the premise that much of the litigation is caused by the punitive attitude of the Brazilian tax administration, which has its actions based on the paradigm of crime. The research is justified insofar as the impact of tax litigation is a relevant issue for the business environment, economic development, for tax collection and the respective support of the State, legitimization of taxation and fiscal solidarity. It was found that the Brazilian tax administration, in order to encourage compliance behavior, resort to traditional methods, however, insufficient for the complexity of the taxpayer's behavior, which is the use of punishment and fear of inspections. This factor, combined with the slowness of the Judiciary, the complexity of the tax legislation, the recurring special payment installments, makes the tax environment unable to encourage the taxpayer to comply with the legislation on a voluntary basis. In view of this it was verified the adequacy of cooperative fiscal compliance to reduce tax litigation, which consists of a new form of relationship, based on the service paradigm, based on trust, transparency, respect and legal certainty. Key compliance concepts, pillars and issues were explored, foreign experiences and compliance programs in effect in Brazil were analysed. In addition, it analyzed the relationship of the new form of relationship with the supremacy of the public interest, legitimacy of taxation and solidarity. Finally, some criticisms and challenges of Brazilian programs were outlined. The research allows us to conclude that cooperative tax compliance can bring benefits to the reduction of tax litigation in Brazil, as it acts to prevent the emergence of tax conflicts, through a more adequate understanding of the taxpayer's reality. In addition, it enables a strategic action by the tax authorities and engages the taxpayer to be regularized for the future, being a more legitimate means of persuasion. The methodology to be used will be qualitative and will consist of the analysis of bibliographic material on the subject in question, notably articles, dissertations, theses, scientific journals and other documents of academic level, printed or available on specialized websites. Thus the work was developed under the perspective of the hypothetical-deductive method, in which the hypotheses elaborated based on the indicated bibliographic survey will be submitted to several critical tests, in order to offer a safe and methodologically adequate conclusion.